You are on page 1of 18

134

6 Dynamics of Systems of Particles

(Most of the material presented in this chapter is taken from Thornton and Marion, Chap.
9.)
In this chapter we study the dynamics of systems composed potentially of a large number
of particles, and inquire on conservation theorems and the behavior of systems that
exhibit mass loss (e.g., rockets).
6.1 Centre of Mass
For a system composed of n particles, the total mass M is given by

, M m

(6.1)

where m

is the mass of the th particle, with 1, ... , n = . If each particle is

(mathematically) connected to the origin of the system through a position vector

r , then
the centre of mass vector is defined as

1
. m
M

=

R r (6.2)

For a continuous system, the summation over is replaced with an integral over an
infinitesimal amount of mass dm such that

1
. dm
M
=

R r (6.3)

It is important to realize that the position vector R of the centre of mass depends on the
origin chosen for the coordinate systems.
6.2 The Conservation of Linear Momentum
The force acting on particle of a system of particles is composed of the resultant of all
forces external to the system
( ) e

F , and the resultant of the internal forces

f stemming
from its interaction with the other particles that are part of the system. If we define these
internal interaction forces as

f , the resulting force

f acting on particle is

.

=

f f (6.4)

The total force

F acting on the particle is

135

( )
.
e

= + F F f (6.5)

From Newtons Second Law we can write

( )
,
e

= + p F f (6.6)

or

( )
( )
( )
2
2
,
e
e
d
m
dt

= +
= +

r F f
F f
(6.7)

where no summation on repeated index is implied.
Summing equation (6.7) over all particles we get

( )
( )
2
2
,
,
e
pairs
d
m
dt

| |
= +
|
\
= + +

r F f
F f f
(6.8)

where we have defined the sum over all external forces on all the particles as

( )
,
e

F F (6.9)

and the second term on the right of equation (6.8) was replaced by a single summation
over every pair of internal interactions between the particles. However, we know from
Newtons Third Law that

= f f . Thus the second term on the right will sum to zero,
as each internal force has an equal and opposite internal force.

We can therefore write, from equation (6.8) that

. M = R F

(6.10)

where we have used Eqn (6.2) to change the left-hand side. Thus we conclude that the
the centre of mass moves like a particle of mass M acted upon by all the external forces
acting on all the individual particles (but is unaffected by any internal forces).

If we now consider the total linear momentum of the system, we have

136

,
m
d
m M
dt

=
| |
= =
|
\

P r
r R

(6.11)

where we have again used the equation for the centre of mass. Thus the total linear
momentum of the system is the same as that of a particle of mass M (the total mass of the
system) moving at the velocity of the centre of mass.

This equation can be used to express the conservation of momentum since
, M = P R

(6.12)

so

. M = = P R F

(6.13)

and the total linear momentum of the system will be conserved if the external forces are
zero.

We can summarize this result as follows

I. The centre of mass of a system moves as if it were a single particle of mass equal
to the total mass of the system, acted upon by the total external force, and
independent of the internal forces (as long as

= f f (Newtons Third Law)
holds).
II. The total linear momentum of a system is the same as that of a single particle of
mass M located at the position of the centre of mass and moving in the manner
the centre of mass moves.
III. The total linear momentum for a system free of external forces is a constant and
equal to the linear momentum of the centre of mass (the law of conservation of
linear momentum for a system).
6.3 The Conservation of Angular Momentum
As we saw in the previous chapter on central force motion, it is often more convenient to
define the positions of the particles composing a system by vectors

r originating at the
centre of mass (see Figure 6-1). The position vector

r of particle in the inertial frame

is

.

= + r R r (6.14)

The angular momentum of the th particle around the COM is given by

137
,

= L r p (6.15)

and summing over all particles

Figure 6-1 Description of the position of a particle using its position vector from the
centre of mass of the system.

( ) ( )
( ) ( )
( ) ( ) ( ) ( ) .
m
m
m

= = =
( = + +

( = + + +

L L r p r r
R r R r
R R R r r R r r

(6.16)

The second and third terms on the right hand side equal zero from

( ) ( ) ( ) ( ) ( )
2 0,
d
m m
dt
d
m m
dt

(
( + = +
(

| | | |
= + =
| |
\ \

R r r R R r R r r R
R r r R

(6.17)

where we have used the rule for differentiating a cross product

( ) ( ) ( )
d
dt

= + R r R r R r

and from equations (6.2) and (6.14),

138
0. m

r (6.18)

Equation (6.16) now becomes

( )
( ).
m m

| |
= +
|
\
= +

L R R r r
R P r p

(6.19)

Note: we have pulled the summation into the cross-product in the first term on the right.
We can do this because R is constant and so the value of this term is unaffected.

We, therefore, have this important result

IV. The angular momentum about an origin is the sum of the angular momentum of
the centre of mass about that origin and the angular momentum of the system
about the position of the centre of mass.

The time derivative of the total angular momentum is

( )
( )
( )
( )
( ) ( ) ( )
,
e
e

<
= =
| |
= +
|
\
(
= + +

L L r p
r F r f
r F r f r f

(6.20)

where
<

means a sum over and with < .

We know, however, from Newtons Third Law that

= f f so that equation (6.20) can
be re-written

( )
( ) ( )
.
e

<
(
= +

L r F r r f

(6.21)

If we further limit ourselves to internal forces

f that are also directed along the straight

line joining the two interacting particles (i.e., along

r r ), we must have the following

( )
0.

= r r f (6.22)

139
This reflects the fact that internal forces produce no net torque. The time derivative of the
total angular momentum is then

( )
( )
,
e

L r F

(6.23)

or if we express the right hand side as a sum of the external torque applied on the
different particles
( ) e

N

( ) ( )
.
e e

= =

L N N

(6.24)

We, therefore, have the following results

V. If the net resultant external torque about an axis vanishes, then the total angular
momentum of the system about that axis remains a constant in time.

Furthermore, since we found that the total internal torque also vanishes, i.e.,

( )
0,

<
| |
(
= =
|

\

r f r r f (6.25)

and we can state that

VI. The total internal torque must vanish if the internal forces are central (i.e.,

= f f and the internal forces between two interacting particles are directed
along the line joining them), and the angular momentum of an isolated system
cannot be altered without the application of external forces.
6.4 The Energy of the System
Consider a system of particles that evolves from a starting configuration 1 to an ulterior
configuration 2 where the positions

r of the particles may have changed in the

process. We can write the total work done on the system as the sum of the work done on
individual particles

140

2
12
1
2 2
1 1
2
2 2
2
1 1
2
2
2 1
1
1 1
2 2
1
,
2
W d
d d d
m dt m dt
dt dt dt
dv d
m dt m v dt
dt dt
d m v T T

=
= =
| |
= =
|
\
| |
= =
|
\

F r
v r v
v
(6.26)

where

2
1
.
2
T T m v

= =

(6.27)

Using equation (6.14) we can write

( ) ( )
( ) ( )
( ) ( )
2
2
2
2
2 ,
v
V v

= = + +
= + +
= + +
r r R r R r
R R r R r r
r R

(6.28)

where and v V

= = r R

. Inserting equation (6.28) into equation (6.27), while using

the earlier result that states that 0 m

r , we find that

( )
2
2
1 1
.
2 2
T MV m v

= +

(6.29)

In other words

VII. The total kinetic energy of the system is equal to the sum of the kinetic energy
of a particle of mass M moving with velocity of the centre of mass and the
kinetic energy of motion of the individual particles relative to the centre of
mass.

Alternatively, we can rewrite first of equations (6.26) by separating the total force applied
on each particle in its external and internal components

( )
2 2
12
1 1
,
.
e
W d d

= +

F r f r (6.30)

141
Note that the second term on the left-hand side, were summing over all pairs of particles
to account for all their mutual interactions, but we exclude the case = since the
particles dont exert forces on themselves, only other particles. If the forces involved are
conservatives, we can then derive them from potentials such that

( )
,
e
U
U

=
=
F
f
(6.31)

where and U U

are independent potential functions. The gradient operator

is a
vector operator meant to apply to the coordinate components of the th particle (i.e.,
is the index that specifies a given particle, and does not represent a coordinate such as
, , or x y z ). The relationship between the indices is illustrated below in colour.

( , , ) ( , , ) ( , , )
x y z
x y z
U U U
U
x y z
U x y z U x y z U x y z
U
x y z

= + +

= + +

e e e
e e e
(6.32)

Below weve spelled it out for the internal forces, noting that these forces depend on the
positions of both particles in an , pair (since the strength and direction of these forces
depend on their relative positions), but were taking the gradient (actually determining
the force) at the position of only one of the particles

( , , , , , ) ( , , , , , ) ( , , , , , )
x y z
x y z
U U U
U
x y z
U x y z x y z U x y z x y z U x y z x y z
U
x y z

= + +

= + +

e e e
e e e
(6.33)

The first term on the right hand side of equation (6.30) can be written as

142

( )
( )
( )
2 2
1 1
2
1
2
1
2
1
2
1
.
e
x y z x y z
d U d
U U U
dx dy dz
x y z
U U U
dx dy dz
x y z
dU
U

=
| |
= + + + +
|

\
| |
= + +
|

\
=
=

F r r
e e e e e e
(6.34)

The last term of the same equation is transformed to

2 2 2
1 1 1
,
d d d

< >
= +

f r f r f r (6.35)

where we have broken the summation into two parts, which can be understood by looking
at the table below. The first term on the left-hand side is the sum of all the terms with
<, or the terms in the upper-right of the table, while the terms with > are in the
lower-left hand side of the table. Note that the diagonal is empty, because the particles
dont exert forces on themselves, also that the table only goes to ==5 but could go to
any number of particles.

=1 =2 =3 =4 =5
=1
f
12
dx
1
f
13
dx
1
f
14
dx
1
f
15
dx
1

=2
f
21
dx
2
f
23
dx
2
f
24
dx
2
f
25
dx
2

=3
f
31
dx
3
f
32
dx
3
f
34
dx
3
f
35
dx
3

=4
f
41
dx
4
f
42
dx
4
f
43
dx
4
f
45
dx
4

=5
f
51
dx
5
f
52
dx
5
f
53
dx
5
f
54
dx
5

We can combine these two terms back into one by switching the indices on the second
term appropriately (second line, below) and then using the fact that the forces are equal
and opposite so that

= f f (final step, below).

( )
( )
2 2 2
1 1 1
,
2
1
2
1
.
d d d
d d
d d

< >
<
<
= +
= +
=

f r f r f r
f r f r
f r r
(6.36)
143

Before we use the last of equations (6.31) to further transform equation (6.35), we
consider the following differential dU

obtained simply as shown below from the chain

rule realizing that ( , , , , , ) U U x y z x y z

= (the step that converts to a dot product
of vectors may be made clearer by looking at the derivation (6.34) above)

( ) ( )
( ) ( )
dU U U U U dx U dy U dz
dx dy dz
dt x dt y dt z dt x dt y dt z dt
U U U U U U
dU dx dy dz dx dy dz
x y z x y z
dU U d U d
d d

= + + + + +

= + + + + +

= +
= +
=
r r
f r f r
f
( )
, d d

r r
(6.37)

where we have used the fact that the forces any pair of particles exert on each other are
equal and opposite, or rather that U U

= = = f f (note also that
U U

= ).

We note that this result is relevant to our earlier work and so, combining this result (6.37)
with equations (6.30), (6.34), and (6.35), we get

( )
2 2
1 1
,
2
1
d d d
dU
U

<
<
<
=
=
=

f r f r r
(6.38)

or that the total work done is

2
2
12
1
1
. W U U

<
=

(6.39)

If we define the total potential energy as the potential due to all external and internal
sources

, U U U

= + (6.40)

we get
144

2
12 1 2
1
. W U U U = = (6.41)

Combining equation (6.41) and the last of equations (6.26), we find that

2 1 1 2
T T U U = (6.42)

or,

1 1 2 2
, T U T U + = + (6.43)

and finally

1 2
. E E = (6.44)

We have therefore proved the conservation of energy for a system of particles where all
the forces (internal and external) can be derived from potentials that are independent of
time; such a system is called conservative.

VIII. The total energy for a conservative system is constant.
6.5 Rocket Motion
We now work out two examples dealing the motion of rockets. The first one concerns a
rocket in free space, whereas the second deals with vertical ascent under gravity.
6.5.1 Rocket Motion in Free Space
We consider the case where a rocket is moving under the influence of no external forces.
Therefore, the total linear momentum (of the rocket plus any fuel ejected as exhaust) will
be conserved. We assume that the rocket is moving in an inertial reference frame in the x
direction at velocity
x
v = v e . During a infinitesimal time interval dt an infinitesimal
amount of mass ' dm is ejected from the rocket engine with a speed
x
u = u e with
respect to the ship (see Figure 6-2). If we define the quantities ( ) ( )
x
t p t = p e as the
momentum at time t , we can write

145

Figure 6-2 A rocket moves in free space at velocity v. In the time interval dt , a mass
dm is ejected from the rocket engine with velocity u with respect to the rocket ship.

( )
( ) ( ) ( ) ( ).
p t mv
p t dt m dm v dv dm v u
=
+ = + +
(6.45)

Since we must have conservation of linear momentum (because there are no external
forces acting on the rocket), we have

( ) ( )
( )( ) ( )
,
p t p t dt
mv m dm v dv dm v u
mv mv mdv dm v dm dv dm v u dm
= +
= + +
= + +
(6.46)

and

, mdv u dm = (6.47)

or

.
dm
dv u
m

= (6.48)

In going from the last of equations (6.46) to equation (6.47) we have neglected the term
dm dv , which is a second order term. What does this mean? Simply that a term involving
the product of two infinitesimal quantities (and dm dv is the only term like this in (6.46))
should be smaller than terms involving only one infinitesimal quantity and so we decide
to neglect it. This is an approximation, but turns out to be a good one, again because it is
such a small term that its neglect has little impact on the answer.

146
The (positive) amount of mass dm ejected from the rocket is, obviously, equal to the
amount of mass lost by the ship. We can then write

, dm dm = (6.49)

and

.
dm
dv u
m
= (6.50)

So the increase in speed the rocket feels (dv) is related to the exhaust speed of the rocket
relative to itself (u) and the rate of mass loss and the rocket mass.

If
0 0
and m v are, respectively, the initial mass and speed of the rocket we can integrate
equation (6.50) to yield

0 0
0
0
0
0
ln
ln ,
v m
v m
dm
dv u
m
m
v v u
m
m
v v u
m
=
| |
=
|
\
| |
= +
|
\

(6.51)

where the exhaust velocity u was assumed to be a constant (i.e., not a function of
or v m) and the mass of the rocket is m. Thus to maximize the speed of the rocket, one
needs to maximize the exhaust velocity u and the ratio
0
m m. If m is mass of the
payload put into space, then a large ratio
0
m m means that a lot of the initial mass of the
rocket must be fuel, which means the final velocity of the payload will be larger.

One difficulty with rocket flight is the logarithmic nature of the right hand side of (6.51).
We would like to get as large an increase in velocity as possible in order to get to our
destination as quickly as possible. We can improve our final velocity by increasing u, but
there are limits to the exhaust velocities of ordinary chemical rockets. So were left with
improving the
0
m m ratio, the total initial mass to the final payload mass. If we increase
this ratio say from 50% to 90% (meaning that the final mass of the spacecraft in space
drops to only 1/5
th
of its initial value) we only get an improvement in final velocity of
147
( ) ( ) ( )
100 100
ln ln
10 50
ln 10 ln 2 \
(2.30 0.69)
1.61
u
u
u
u
| | | | | |

| | |
\ \ \

So for a tremendous reduction in the size of the spacecraft (by a factor of 5 in this case),
we only get a modest increase in our final velocity. This is the reason why engineers have
conceived multistage rockets, where independent fuel containers can be jettisoned when
they empty.
For example, a multistage rocket might have an initial mass
0
m , while its mass after the
so-called first-stage fuel container has emptied is

1
,
a b
m m m = + (6.52)

where and
a b
m m are the mass of the first-stage payload and first-stage fuel container,
respectively. We can express the terminal speed
1
v reached by the rocket after all the fuel
of the first-stage fuel container has burnt out with the last of equations (6.51)

0
1 0
1
ln .
m
v v u
m
| |
= +
|
\
(6.53)

At that time, the mass
b
m of the first-stage fuel container is released into space, and the
second-stage rocket ignites. We now have
a
m for the starting mass of space ship (second
stage), and
2
m for its mass after the second-stage fuel container has burnt out. The
terminal velocity is given by

2 1
2
0
0
1 2
0
0
1 2
ln
ln ln
ln .
a
a
a
m
v v u
m
m m
v u u
m m
m m
v u
m m
| |
= +
|
\
| | | |
= + +
| |
\ \
| |
= +
|
\
(6.54)

The term ( )
0 1 2 a
m m mm can be made larger than ( )
0 1
m m . Consider the rocket below.
148

( )
0 1 2 a
m m mm = 4 while ( )
0 1
m m =3 if there was no jettisoning of the first stage when it
was empty. Note we have to use the appropriate m
1
for the second ratio ( )
0 1
m m =3, that
is the total initial mass (still 6), and the total final mass of rocket in space when all fuel is
gone (1+1=2), so the ratio is 3. So we can gain by using a multistage rocket, but getting
high speeds from rocket flight remains a difficult problem because of the logarithmic
term.

As a matter of terminology, engineers and scientists usually give the following definition
to the commonly used force term thrust

Thrust ,
dm
u
dt
(6.55)

which is always greater than zero since 0 dm dt < .
6.5.2 Vertical Ascent Under Gravity
We now consider the case of a rocket that is attempting to break free from the Earths
gravitational pull. In order for the problem to be tractable analytically, we will assume
that the rocket has only a vertical motion (i.e., no horizontal movement), there is no air
resistance, and the gravitational field is constant with height. From Figure 6-3 we see that

149

,
y
y
v
g
=
=
v e
g e
(6.56)

and similar equations for the other quantities involved in the problem.
We can use the results of the previous case of motion in free space, but we no longer
have
( )
0
e
= F . As before, the ejected mass is given by dm dm = . From Newtons
Second Law, the external force is

Figure 6-3 A rocket in vertical ascent under Earths gravity. A mass dm is ejected
from the rocket engine, during a time interval dt , with a velocity u with respect to the
rocket ship.

( )
( ) ,
e
dp d
F mv
dt dt
= = (6.57)

or

( )
( ) ( )
( ) ( ) ( )
,
e
F dt dp p t dt p t
m dm v dv v u dm mv
mdv u dm
= = +
= + +
= +
(6.58)

where we have neglected any second order terms (terms with more than one infinitesimal
quantity). Dividing this result by dt we find

( )
.
e
F mg mv um = = + (6.59)

150
We can manipulate equation (6.59) to isolate dv

.
u dm
dv g dt
m dt
dm
g dt u
m
| |
= +
|
\
=
(6.60)

Integration of this last equation yields

0
ln ,
m
v gt u
m
| |
= +
|
\
(6.61)

with
0
m the initial mass of the rocket. We should also note that since the burn rate is
assumed constant, it must also be true that the mass loss is constant. That is,

0,
dm
dt
= < (6.62)

or with a simple time integration

0
. m m t = (6.63)

We can use equation (6.63) to substitute for t in equation (6.61) to express the speed of
the rocket as a function of its mass only

( )
0
0
ln .
m g
v m m u
m
| |
= +
|
\
(6.64)

Example:

Consider the first stage of a Saturn V rocket used for the Apollo moon program. The
initial mass is 2.8 million kg and the mass of the first-stage fuel is 2.1 million kg. Assume
a mean thrust of 37 million N. The exhaust velocity is 2600 m/s. Calculate the speed of
the first stage at burnout.

6
4
thrust 37 10 N
1.42 10 kg/s
2600m/s
dm
dt u

= = =

The final rocket mass is 700,000 kg so we can determine the rocket speed at burnout
using (6.64)

151

( )
( )
0
0
6
6
4 6
3
ln .
9.8m/s 2.8 10 kg
2.1 10 kg (2600m/s) ln
1.42 10 kg/s 0.7 10 kg
2.16 10 m/s
2.16km/s
m g
v m m u
m
| |
= +
|
\
| |
= +
|

\
=
=
(6.65)